Global estimates and determinants of antituberculosis drug pharmacokinetics in children and adolescents: a systematic review and individual patient data meta-analysis - Gafar, Fajri; Wasmann, Roeland E; McIlleron, Helen M; Aarnoutse, Rob E; Schaaf, H Simon; Marais, Ben J; Agarwal, Dipti; Antwi, Sampson; Bang, Nguyen D; Bekker, Adrie; Bell, David J; Chabala, Chishala; et al. (The European respiratory journal, 2023)
Suboptimal exposure to antituberculosis (anti-TB) drugs has been associated with unfavourable treatment outcomes. We aimed to investigate estimates and determinants of first-line anti-TB drug pharmacokinetics in children and adolescents at a global level. We systematically searched MEDLINE, Embase and Web of Science (1990-2021) for pharmacokinetic studies of first-line anti-TB drugs in children and adolescents. Individual patient data were obtained from authors of eligible studies. Summary estimates of total/extrapolated area under the plasma concentration-time curve from 0 to 24 h post-dose (AUC ) and peak plasma concentration ( ) were assessed with random-effects models, normalised with current World Health Organization-recommended paediatric doses. Determinants of AUC and were assessed with linear mixed-effects models. Of 55 eligible studies, individual patient data were available for 39 (71%), including 1628 participants from 12 countries. Geometric means of steady-state AUC were summarised for isoniazid (18.7 (95% CI 15.5-22.6) h·mg·L ), rifampicin (34.4 (95% CI 29.4-40.3) h·mg·L ), pyrazinamide (375.0 (95% CI 339.9-413.7) h·mg·L ) and ethambutol (8.0 (95% CI 6.4-10.0) h·mg·L ). Our multivariate models indicated that younger age (especially <2 years) and HIV-positive status were associated with lower AUC for all first-line anti-TB drugs, while severe malnutrition was associated with lower AUC for isoniazid and pyrazinamide. -acetyltransferase 2 rapid acetylators had lower isoniazid AUC and slow acetylators had higher isoniazid AUC than intermediate acetylators. Determinants of were generally similar to those for AUC . This study provides the most comprehensive estimates of plasma exposures to first-line anti-TB drugs in children and adolescents. Key determinants of drug exposures were identified. These may be relevant for population-specific dose adjustment or individualised therapeutic drug monitoring.